Approximate Solutions of Klein-Gordon Equation with Kratzer Potential - H. Hassanabadi; H. Rahimov; S. Zarrinkamar (Advances in High Energy Physics)
Approximate solutions of the D-dimensional Klein-Gordon equation are obtained for the scalar and vector general Kratzer potential for any l by using the ansatz method. The energy behavior is numerically discussed.